Summary of the Affordable Care Act - Meltzer, C.C. (American Journal of Neuroradiology, 2011)
SUMMARY: The voluminous bill known as the PPACA of 2010 enabled substantial changes to our health care delivery system, some of which remain to be enacted for several years to come. While the overarching goal is to align incentives and improve quality and access, implementing PPACA initiatives in a highly complex environment is fraught with economic and political implications. The purpose of this and future AJNR Health Care Vignettes is to provide relevant updated information as it becomes available. CMSCenters for Medicare and Medicaid ServicesEHRelectronic health recordGDPgross domestic productHITECHHealth Information Technology for Economic and Clinical HealthMRAMR angiographyPETpositron-emission tomographyPPACAPatient Protection and Affordable Care Act